Activation of Adenosine-Monophosphate–Activated Protein Kinase Abolishes Desflurane-Induced Preconditioning Against Myocardial Infarction In Vivo - Lotz, Christopher; Fisslthaler, Beate; Redel, Andreas; Smul, Thorsten M.; Stumpner, Jan; Pociej, Joanna; Roewer, Norbert; Fleming, Ingrid; Kehl, Franz; Lange, Markus (Journal of cardiothoracic and vascular anesthesia, 2011)
Myocardial ischemia is accompanied by a rapid activation of adenosine-monophosphate–activated protein kinase (AMPK). However, it is unclear whether this represents a potentially beneficial or detrimental event in the course of ischemic injury. The role of AMPK activation in the cardioprotective setting of desflurane-induced preconditioning has not been investigated to date. Hence, the current study was undertaken to address the role of AMPK activation during desflurane-induced preconditioning in vivo. A prospective randomized vehicle-controlled study. A university research laboratory. Male New Zealand white rabbits (n = 44). The animals were subjected to a 30-minute coronary artery occlusion (CAO) followed by 3 hours of reperfusion. Desflurane (1.0 minimum alveolar concentration) was administered for 30 minutes and discontinued 30 minutes prior to CAO. Different groups of animals received the AMPK activator, 5-aminoimidazole-4-carboxamide-1-b-riboside (AICAR), alone or in combination with desflurane. Infarct size was determined gravimetrically; AMPK activity and myocardial glycogen content were measured using specific assays. Phosphorylation of the AMPK substrate, acetyl-CoA carboxylase, was assessed by immunoblotting. Data are mean ± standard error of the mean. Desflurane significantly reduced the myocardial infarct size (36.7 ± 1.9%, p < 0.05) compared with the control group (61.6% ± 3.0%), concomitant with increased myocardial tissue levels of glycogen (2.09 ± 0.07 μg, p < 0.05). Activation of the AMPK by AICAR alone did not protect against ischemic injury (65% ± 3.3), but did abolish the cardioprotection elicited by desflurane (61.8% ± 4.2%) at the same time as increasing myocardial glycogen consumption (1.42 ± 0.15 μg/mL). The results obtained show that the pharmacologic activation of AMPK abolishes cardioprotection elicited by desflurane.